2008
DOI: 10.1186/bf03352770
|View full text |Cite
|
Sign up to set email alerts
|

Gravity anomalies and the geologic block structures in and around the aftershock area of the 2007 Noto Hanto Earthquake

Abstract: The 2007 Noto Hanto Earthquake occurred on 25 March. We have constructed a detailed gravity anomaly map over the Noto peninsula. Four block boundaries which are identified by morphological/geological studies are also recognized on the gravity anomaly map. Various other observations indicate that the mainshock ruptured only one of the blocks, the Kuwatsuka block, although aftershocks are distributed over two blocks, the Kuwatsuka and the Saruyama blocks. The Bouguer anomalies over the Kuwatsuka block are relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…In the Saruyama block, M1 has not been identified because of its Rias-like coastline (Ota and Hirakawa, 1979). In addition, the detailed Bouguer anomaly map indicates that the basement depth of the northwestern part of the Kuwatsuka block is shallower than that of the southwestern part of the Saruyama block (Honda et al, 2008). These features mentioned above do not contradict the observed coseismic vertical displacement along the coast (Fig.…”
Section: Crustal Deformation Since the Pleistocenementioning
confidence: 50%
See 1 more Smart Citation
“…In the Saruyama block, M1 has not been identified because of its Rias-like coastline (Ota and Hirakawa, 1979). In addition, the detailed Bouguer anomaly map indicates that the basement depth of the northwestern part of the Kuwatsuka block is shallower than that of the southwestern part of the Saruyama block (Honda et al, 2008). These features mentioned above do not contradict the observed coseismic vertical displacement along the coast (Fig.…”
Section: Crustal Deformation Since the Pleistocenementioning
confidence: 50%
“…9). These block structures are also recognized by a detailed Bouguer anomaly map (Honda et al, 2008). The central aftershock area lies approximately in the Kuwatsuka block and the northeastern area in the Saruyama block.…”
Section: Discussionmentioning
confidence: 99%
“…From a comparison of gravity anomalies and aftershock distributions, Honda et al (2002) have shown that the source area of the 2000 Tottori-ken Seibu earthquake was controlled by a geological boundary. Gravity analysis around the aftershock region of the 2007 Noto Hanto earthquake showed that the rupture size of the earthquake was constrained by block structures in the Noto Peninsula (Honda et al 2008). In Kyushu, Nishijima and Fujimitsu (2015) reveal the fault structure of the Minou fault zone H in a g u T a k a n o -S h ir a h a t a H i n a g u F a u l t Z o n e F u t a g a w a F a u l t Z o n e…”
Section: Introductionmentioning
confidence: 99%